EVALUASI PENGGUNAAN ANTIBIOTIK PROFILAKSIS PADA PASIEN BEDAH SESAR DI INSTALASI BEDAH SENTRAL RUMAH SAKIT XY MANADO - Tampa’i, Randy; Ngala, Nancy; Wua, Diah (Jurnal Farmasindo: Jurnal Penelitian dan Pengabdian Masyarakat, 2020)
Sectio Caesarea is a procedure to remove a fetus through surgery on the abdomen and uterus. Sectio Caesarea is performed as an alternative if normal delivery is not possible to deliver birth on the birth canal. Sectio Caesarea can be performed both by design or emergency on high-risk pregnancies. The risk of infection in Sectio Caesarea surgery can be reduced by giving antibiotic prophylaxis therapy. The purpose of this study to evaluate the use of antibiotic prophylaxis in Sectio Caesarea patients at Central Surgical Installation XY Hospital in Manado during 2019. The study has been performed observational, the data were obtained by retrospective and study of patient's fully sampling of medical records. The study result showed that antibiotic prophylaxis in 58 patients with Caesarea surgery was used 55 patients with Ceftriaxone (94,8%) and 3 patients with Cefazolin (5,2%). This shows the selection of the type of cesarean section antibiotic prophylaxis is not appropriate with the General Guidelines for the Use of Antibiotics by the Peraturan Menteri Kesehatan Republik Indonesia in 2011, because there are only 5.2% of the first generation cephalosporin class antibiotics according to the guidelines for cesarean section prophylaxis. Based on the duration of administration, the route of administration and the dose of prophylaxis antibiotics in patients with the cesarean section is by the General Guidelines for the Use of Antibiotics by the Peraturan Menteri Kesehatan Republik Indonesia in 2011, which is supported by the recommendations of the ASHP Therapeutic Guideline and the Drug Information Handbook Ed.17.